(untitled) (Global Journal of Management and Business Research, 2017)
Tobacco use increases morbidity and mortality and is an established health hazard as it contributes to multiple diseases, including cardiovascular, pulmonary, musculoskeletal, immune diseases, and cancer and asthma (WHO, 2011). Information on factors affecting the tobacco use is useful for policies on tobacco reduction, especially in developing countries. This paper examines the key socio-economic characteristics associated tobacco use using a Demographic Health Survey (DHS) data (2010) in Tanzania. Both logit and multinomial logistic regression models are used to identify key determinants of tobacco consumption choices. The regression analyses of tobacco use in Tanzania identify age, urban residence, no education, primary, poorest, poor and never married as factors associated with the choice of tobacco use among males, while age, no education, primary, poorest, poor, unemployed and being an unskilled and domestic employer were significantly associated with female tobacco use. The prevalence of tobacco use in Tanzania is high as compared to the rates in other SSA countries. Although the government in collaboration with WHO continues to enact policies to address the problem, there is a need for effective implementation and enforcement of tobacco reduction policies. There is also the need for health education to modify social norms and also reduce tobacco use in Tanzania.